2015
DOI: 10.1093/humrep/dev240
|View full text |Cite
|
Sign up to set email alerts
|

Why do niches develop in Caesarean uterine scars? Hypotheses on the aetiology of niche development

Abstract: Caesarean section (CS) results in the occurrence of the phenomenon ‘niche’. A ‘niche’ describes the presence of a hypoechoic area within the myometrium of the lower uterine segment, reflecting a discontinuation of the myometrium at the site of a previous CS. Using gel or saline instillation sonohysterography, a niche is identified in the scar in more than half of the women who had had a CS, most with the uterus closed in one single layer, without closure of the peritoneum. An incompletely healed scar is a long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
230
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(241 citation statements)
references
References 65 publications
3
230
0
8
Order By: Relevance
“…Several hypotheses may explain CSD development: a very low incision through the cervical tissue, impaired wound healing, adhesion formation, inadequate suturing or incomplete closure of the uterine scar due to endometrial closure technique [8]. A recent meta-analysis reported a similar incidence of CSD in women who received single-layer closure (25.5% vs 43.0%; RR 0.77, 95% CI 0.36 to 1.64; 5 trials; 350 participants; low quality of evidence) compared to women who received double-layer closure [9].…”
Section: Discussionmentioning
confidence: 99%
“…Several hypotheses may explain CSD development: a very low incision through the cervical tissue, impaired wound healing, adhesion formation, inadequate suturing or incomplete closure of the uterine scar due to endometrial closure technique [8]. A recent meta-analysis reported a similar incidence of CSD in women who received single-layer closure (25.5% vs 43.0%; RR 0.77, 95% CI 0.36 to 1.64; 5 trials; 350 participants; low quality of evidence) compared to women who received double-layer closure [9].…”
Section: Discussionmentioning
confidence: 99%
“…15 While the number of the cases in women who become pregnant after the repair of post-growing niches, is limited, previa and dehiscence wasn't reported. 13 As the repair of the niches presenting abnormal uterine bleeding symptoms, is being suggested, the pre-pregnancy repair should also be considered in terms of pregnancy complications in larger niches.…”
Section: Discussionmentioning
confidence: 99%
“…First, concerns the location of the incision that was made too low in the cervical part of uterus, that contains mucous glands. Mucus produced in the time of wound healing may dilate the sutured edges of the myometrial tissue [18]. The confirmation for this theory was the study which stated that isthmocoele was found more frequently in patients who had caesarean section performed on maximal dilation, when finding proper place between uterus and cervix is more difficult [19].…”
Section: Etiopathogenesismentioning
confidence: 99%
“…The authors also state that it may be the reason for recurrence of isthmocoele in 5% of patients after repairing surgery [20,21]. There are some other theories involving obesity as a risk factor, but the mechanism of action is unknown [18,22].…”
Section: Etiopathogenesismentioning
confidence: 99%